CFTR Modulators Restore Acidification of Autophago-Lysosomes and Bacterial Clearance in Cystic Fibrosis Macrophages - Badr, Asmaa; Eltobgy, Mostafa; Krause, Kathrin; Hamilton, Kaitlin; Estfanous, Shady; Daily, Kylene P.; Abu Khweek, Arwa; Hegazi, Ahmad; Anne, Midhun N. K.; Carafice, Cierra; Robledo-Avila, Frank; Saqr, Youssra; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Cystic fibrosis (CF) human and mouse macrophages are defective in their ability to clear bacteria such as Burkholderia cenocepacia. The autophagy process in CF (F508del) macrophages is halted, and the underlying mechanism remains unclear. Furthermore, the role of CFTR in maintaining the acidification of endosomal and lysosomal compartments in CF cells has been a subject of debate. Using 3D reconstruction of z-stack confocal images, we show that CFTR is recruited to LC3-labeled autophagosomes harboring B. cenocepacia. Using several complementary approaches, we report that CF macrophages display defective lysosomal acidification and degradative function for cargos destined to autophagosomes, whereas non-autophagosomal cargos are effectively degraded within acidic compartments. Notably, treatment of CF macrophages with CFTR modulators (tezacaftor/ivacaftor) improved the autophagy flux, lysosomal acidification and function, and bacterial clearance. In addition, CFTR modulators improved CFTR function as demonstrated by patch-clamp. In conclusion, CFTR regulates the acidification of a specific subset of lysosomes that specifically fuse with autophagosomes. Therefore, our study describes a new biological location and function for CFTR in autophago-lysosomes and clarifies the long-standing discrepancies in the field.